In vitro antifungal activity and cytotoxic effect of essential oils and extracts of medicinal and aromatic plants against Candida krusei and Aspergillus fumigatus (2010)
ABSTRACT: The plants are usually used in traditional medicine as antimicrobial agents and their essential oils and extracts have been known to possess antifungal activity. The aim of this study was to evaluate in vitro the activity of 32 essential oils and 29 extracts against C. krusei and A. fumigatus as well as the cytotoxic effect on Vero cells. Time-kill curve and interaction between antifungals and the most active sample against C. krusei, was also evaluated. The oils from C. ambrosioides and the extract of M. cucullata showed antifungal activity against C. krusei (GM-MIC 7.82 and 31.25 µg/mL, respectively). L. citriodora was actives against C. krusei and A. fumigates (GM-MIC = 99.21 µg/mL and 62.5 µg/mL respectively). Time-kill assays done with C. ambrosioides oil showed fungicidal activity at 4x MIC. The interaction of C. ambrosioides oil with itraconazole and amphotericin B was tested following the chequerboard technique. No interaction was detected for the combination of C. ambrosioides oil with amphotericin B and itraconazole (FICI range = 1.03-1.06 and 1.03-1.00, respectively). Cytotoxicity assays for all samples were carried out with MTT. Only the oil from Hedyosmun sp. and L. dulcis were cytotoxic.